Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

Clay-mediated selective hydrolysis of 5 `-O-acetyl-2 `,3 `-isopropylidene/cyclohexylidene nucleosides - Gurjar, Mukund K.; Mondal, Dhananjoy; Ravindranadh, S. V.; Chorghade, Mukund S. (Synthetic Communications, 2006)
A generalized procedure for the selective hydrolysis of 5'O-acetyl-2',3'-isopropylidene/cyclohexylidene nucleosides with a solid catalyst, Montmorillonite K-10 in refluxing methanol, to furnish 5'-O-acetyl-nucleosides is described.
Keywords: 5-O-acetylnucleosides; isopropylidene-nucleoside hydrolysis; montmorillonite K 10